The Mechanisms of Cucurbitacin E as a Neuroprotective and Memory-Enhancing Agent in a Cerebral Hypoperfusion Rat Model: Attenuation of Oxidative Stress, Inflammation, and Excitotoxicity - Liu, Zhiyong; Kumar, Manish; Devi, Sushma; Kabra, Atul (Frontiers in Pharmacology, 2021)
Impaired cerebral hemodynamic autoregulation, vasoconstriction, and cardiovascular and metabolic dysfunctions cause cerebral hypoperfusion (CH) that triggers pro-oxidative and inflammatory events. The sequences linked to ion-channelopathies and calcium and glutamatergic excitotoxicity mechanisms resulting in widespread brain damage and neurobehavioral deficits, including memory, neurological, and sensorimotor functions. The vasodilatory, anti-inflammatory, and antioxidant activities of cucurbitacin E (CuE) can alleviate CH-induced neurobehavioral impairments. In the present study, the neuroprotective effects of CuE were explored in a rat model of CH. Wistar rats were subjected to permanent bilateral common carotid artery occlusion to induce CH on day 1 and administered CuE (0.25, 0.5 mg/kg) and/or Bay-K8644 (calcium agonist, 0.5 mg/kg) for 28 days. CH caused impairment of neurological, sensorimotor, and memory functions that were ameliorated by CuE. CuE attenuated CH-triggered lipid peroxidation, 8-hydroxy-2′-deoxyguanosine, protein carbonyls, tumor necrosis factor-α, nuclear factor-kappaB, myeloperoxidase activity, inducible nitric oxide synthase, and matrix metalloproteinase-9 levels in brain resulting in a decrease in cell death biomarkers (lactate dehydrogenase and caspase-3). CuE decreased acetylcholinesterase activity, glutamate, and increased γ-aminobutyric acid levels in the brain. An increase in brain antioxidants was observed in CuE-treated rats subjected to CH. CuE has the potential to alleviate pathogenesis of CH and protect neurological, sensorimotor, and memory functions against CH.